Effect of Type 2 Diabetes Mellitus on Pulmonary Function: Effect of Type 2 Diabetes Mellitus on Pulmonary Function - Nachimuthu, Kanchana (International Journal of Pharmaceutical & Biological Archive, 2020)
Diabetes mellitus (DM) is a chronic metabolic and vascular disorder affecting various organs and systems. Many studies have shown impairment of pulmonary functions in diabetics subjects, whereas some studies did not show any changes in pulmonary functions. Therefore, objective of the present study is to find out alterations in the pulmonary functions. Methods Design, Setting, and Participants: This cross-sectional study was conducted in a tertiary care hospital among patients attending medicine department. The sample size was 200. A total of 100 known cases of DM without any acute or chronic lung disease and 100 healthy controls were included in the age group of 40â€“50 years. History of smoking was excluded in both groups. The diabetic subjects had at least 1 year of duration of disease. Intervention: Pulmonary function test (spirometry) was performed with NND TrueFlow Easy Oneâ„¢ diagnostic spirometer. Main Outcome Measures: The forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1) were the primary outcome measures to assess the pulmonary functions. Results: In Phase 1 analysis, diabetic subjects did not show any changes in both FVC and FEV1 when compared with controls. In Pearson correlation test, a significant negative correlation between duration of disease and pulmonary functions, FVC at the level of 0.05 and FEV1 at the level of 0.01 were observed. However, in Phase 2 analysis, a significant reduction in FVC and FEV1 was observed in diabetic subjects with duration of diabetes more than 5 years. Conclusion: The decline in FVC and FEV1 in diabetic subjects is more likely to be the effect of DM. The decline is more pronounced with the duration of the disease.